Cardiovascular Complications in CKD Patients: Role of Oxidative Stress - Elvira O. Gosmanova; Ngoc-Anh Le (Cardiology Research and Practice)
Starting with the early stages, patients with chronic kidney disease (CKD) experience higher burden of cardiovascular disease (CVD). Moreover, CVD complications are the major cause of mortality in CKD patients as compared with complications from chronic kidney failure. While traditional CVD risk factors, including diabetes, hypertension, hyperlipidemia, obesity, physical inactivity, may be more prevalent among CKD patients, these factors seem to underestimate the accelerated cardiovascular disease in the CKD population. Search for additional biomarkers that could explain the enhanced CVD risk in CKD patients has gained increasing importance. Although it is unlikely that any single nontraditional risk factor would fully account for the increased CVD risk in individuals with CKD, oxidative stress appears to play a central role in the development and progression of CVD and its complications. We will review the data that support the contribution of oxidative stress in the pathogenesis of CVD in patients with chronic kidney failure.